2002
DOI: 10.1007/bf02483141
|View full text |Cite
|
Sign up to set email alerts
|

Conception of an isothermal calorimeter for concrete— Determination of the apparent activation energy

Abstract: A B S T R A C T R I~ S U M I~Instrumentation was developed to perform calorimetric tests on concrete in isothermal conditions using 0.11 x 0.22 m cylindrical samples. The purpose of this article is to study the validity of Arrhenius' law and determine the changes occurring in the apparent activation energy of concrete as a function of temperature, by using this technique. Heat of hydration measurements were made for various isothermal curing conditions (10, 20, 30 and 40~ enabling the apparent activation en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…The apparent activation energies of nucleation rate constant ( I ), growth rate constant ( G ), and generalized diffusion constant ( k D ) are 36.0 kJ/mol, 37.5 kJ/mol, and 42.0 kJ/mol, respectively. The average value of these apparent activation energies of various kinetic parameters is closely to the values in the previous researches from Broda . and Ravikumar, who found that the apparent activation energy of the overall hydration reaction of cement is approximately 37.0 ~ 38.0 kJ/mol.…”
Section: Analysis Of the Kinetics Parameterssupporting
confidence: 86%
“…The apparent activation energies of nucleation rate constant ( I ), growth rate constant ( G ), and generalized diffusion constant ( k D ) are 36.0 kJ/mol, 37.5 kJ/mol, and 42.0 kJ/mol, respectively. The average value of these apparent activation energies of various kinetic parameters is closely to the values in the previous researches from Broda . and Ravikumar, who found that the apparent activation energy of the overall hydration reaction of cement is approximately 37.0 ~ 38.0 kJ/mol.…”
Section: Analysis Of the Kinetics Parameterssupporting
confidence: 86%
“…Using the calorimetry data, the maximum heat released (Q') was calculated to derive the degree of hydration (DOH), defined as the heat at any given time divided by the maximum heat released (Q / Q'), as one of the necessary steps to calculate the activation energy (Ea) (42,43). In this calculation, the limestone is considered as inert (44,45).…”
Section: Calorimetry and Activation Energy Calculationmentioning
confidence: 99%
“…In this study, the rate method [43][44][45] has been applied to determine the discussed energy. Following this method, the apparent activation energy, E a , is calculated based on heat evolution rates q 1 and q 2 , consistent with the same evolved heat, Q i , and two curing temperatures, T 1 and T 2 :…”
Section: Experimental Programmentioning
confidence: 99%